The Development of Lumped Mass Dynamic Modeling Methods of Planetary Gearbox for Fault Detection and Diagnosis - Wang, Zhongwei; Howard, Ian (Engineers Australia, 2010)
This paper presents a 9+3*n+1 degree of freedom planetary gearbox lumped-parameter dynamic model including coupled torsional-transverse behaviour of all components. The model includes one sun gear, one ring gear, one carrier arm, n planet gears and one fluid coupling. It also includes the effects of variable tooth mesh stiffness, pitch and profile excitation, variable operating conditions and gear tooth faults (cracking and spalling) for gear fault detection purposes. The equations of motion are included along with a description of the model. Modeling of pitch and profile excitation and localised tooth faults is detailed. The comparison between models with and without localised teeth faults was obtained by using a MATLAB program which was developed to generate equations of motion automatically and to simulate the resulting vibration behaviour. Dynamic vibration results were processed using signal averaging techniques, frequency analysis and some rudimentary diagnostic methods.